2020
DOI: 10.1186/s13046-020-01765-x
|View full text |Cite
|
Sign up to set email alerts
|

Glycometabolic rearrangements--aerobic glycolysis in pancreatic cancer: causes, characteristics and clinical applications

Abstract: Pancreatic cancer is one of the most malignant tumors worldwide, and pancreatic ductal adenocarcinoma is the most common type. In pancreatic cancer, glycolysis is the primary way energy is produced to maintain the proliferation, invasion, migration, and metastasis of cancer cells, even under normoxia. However, the potential molecular mechanism is still unknown. From this perspective, this review mainly aimed to summarize the current reasonable interpretation of aerobic glycolysis in pancreatic cancer and some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 209 publications
(279 reference statements)
1
35
1
Order By: Relevance
“…For example, PDA cancer-associated fibroblasts with a glycolytic phenotype supported oxidative phosphorylation in cancer cells and, consequently, tumor survival and invasive ability [ 196 ]. The same phenomenon was observed in PDA pancreatic stellate cells via HK2 expression [ 195 , 197 ]. One of the mechanisms of the metabolic interaction of stromal and tumoral cells is through the lactate efflux, thus lactate transporters may play a pivotal role [ 198 ].…”
Section: Metabolic Reprogramming To Increase the Immune Response supporting
confidence: 69%
See 1 more Smart Citation
“…For example, PDA cancer-associated fibroblasts with a glycolytic phenotype supported oxidative phosphorylation in cancer cells and, consequently, tumor survival and invasive ability [ 196 ]. The same phenomenon was observed in PDA pancreatic stellate cells via HK2 expression [ 195 , 197 ]. One of the mechanisms of the metabolic interaction of stromal and tumoral cells is through the lactate efflux, thus lactate transporters may play a pivotal role [ 198 ].…”
Section: Metabolic Reprogramming To Increase the Immune Response supporting
confidence: 69%
“…Several reports have shown that targeting the glycolytic pathway can effectively counteract tumor progression, which could also be due to the role of cells that are part of the TME. Increasing needs of nutrients and glucose in tumors could shift immune cells ( Figure 2 ) and stromal cells towards glycolytic behavior [ 195 ]. For example, PDA cancer-associated fibroblasts with a glycolytic phenotype supported oxidative phosphorylation in cancer cells and, consequently, tumor survival and invasive ability [ 196 ].…”
Section: Metabolic Reprogramming To Increase the Immune Response mentioning
confidence: 99%
“…Consistently, Pyruvate treatment reduced the ability of CK to inhibit p‐AKT, p‐mTOR, HK2, and pro‐Cas3 in treated HepG2 cells, strongly indicating that apoptotic effect of CK is closely related to energy depletion in HepG2 cells. Phosphorylation of Akt/mTOR promotes the transportation of glucose and activity of glycolytic enzymes in cancer cells (Cao et al, 2020; Hoxhaj & Manning, 2020). Upregulation of glycolysis enzymes enhances glucose consumption and lactate production (Burns & Manda, 2017; Yu, Chen, Wang, & Chen, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these metabolite profiles could help to distinguish PDAC severity. In PDAC cells, there is an increased uptake of glucose to produce lactate and ATP under aerobic conditions, a phenomenon known as the Warburg effect [37]. Warburg effect promotes PDAC progression by providing a constant energy source for cellular growth and proliferation.…”
Section: Discussionmentioning
confidence: 99%